Geometric Flow Control Lateral Flow Immunoassay Devices (GFC-LFIDs): A New Dimension to Enhance Analytical Performance - E. Eriksson; J. Lysell; H. Larsson; K. Y. Cheung; D. Filippini; W. C. Mak (Research, 2019)
The nitrocellulose (NC) membrane based lateral flow immunoassay device (LFID) is one of the most important and widely used biosensor platforms for point-of-care (PoC) diagnostics. However, the analytical performance of LFID has limitations and its optimization is restricted to the bioassay chemistry, the membrane porosity, and the choice of biolabel system. These bottom neck technical issues resulted from the fact that the conventional LFID design principle has not evolved for many years, which limited the LFID for advanced biosensor applications. Here we introduce a new dimension for LFID design and optimization based on geometric flow control (GFC) of NC membranes, leading to highly sensitive GFC-LFID. This novel approach enables comprehensive flow control via different membrane geometric features such as the width (w) and the length (l) of a constriction, as well as its input angle (θ1) and output angle (θ2). The GFC-LFID (w=0.5 mm, l=7 mm, θ1= 60°, θ2= 45°) attained a 10-fold increase in sensitivity for detection of interleukin-6 (IL-6), compared with conventional LFID, whereas reducing by 10-fold the antibody consumption. The GFC-LFID detects IL-6 over a linear range of 0.1–10 ng/mL with a limit of detection (LoD) of 29 pg/mL, which even outperforms some commercial IL-6 LFIDs. Such significant improvement is attained by pure geometric control of the NC membrane, without additives, that only relaying on a simple high throughput laser ablation procedure suitable for integration on regular large-scale manufacturing of GFC-LFIDs. Our new development on GFC-LFID with the combination of facile scalable fabrication process, tailored flow control, improved analytical performance, and reduced antibodies consumption is likely to have a significant impact on new design concept for the LFID industry.